Paperworks : Canada/USA. - Alberta College of Art Gallery, Calgary (Calgary : Alberta College of Art Gallery, 1983)
Becker, Helmut ; Butler, K. Jack ; Gordon, Coco ; Heon, Michelle ; Keene, Susan Warner ; Lutz, Winifred ; Moses, Cherie ; Morissette, Gilles ; O'Banion, Nance ; Pixley, Anne Flaten ; Rosen, Carol ; Ross, Czashka M.J. ; Seventy, Sylvia ; Soteriou, Alexandra
Paperworks : Canada/USA, Alberta College of Art Gallery, Calgary, September 15 to October 12, 1983
boek